Implementasi Pembelajaran K13 Terhadap Prestasi Belajar Siswa Kelas X IPS Mata Pelajaran Ekonomi Di SMAN 1 Ende - Florentina Kori; Sayful Amrin; Stefanus H. Gusti Ma (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
The aim of this research are to know (1) the implementation of K13 at SMA Negeri 1 Ende in academic year 2016/2017. (2) students achievement of class X of social science department on economics subject at SMA Negeri 1 Ende in academic year 2016/2017 This research used descriptive qualitative approach. The main instrument of this research was researcher ownself. Interview, observation and documentation were the method used for gathering data. Meanwhile, interactive models of Miles and Huberman used for data analysis. he result shows that (1) the implementation of K13 already applied properly. (2) after K13 implemented during teaching and learning process, the achievement of students can be seen through the spirit of the students to find out what they do not know yet are high. Beside that, the students are also active participate in classroom, and they tend to ask and discuss more. The conclusion and suggestion addressed to; first is to the teacher who handle social science economic subject is expected to keep trying on increasing students understanding about K13; second is to the students as the object where K13 implemented are expected to be more active and participate in classroom activities so that their achievement can be increased.